دور الأمن السيبراني في مكافحة الجرائم المالية والالكترونية (الابتزاز الإلكتروني الموجه ضد النساء نموذجاً) (Comprehensive Journal of Science, 2026)
This study aims to identify the nature of electronic blackmail, as one of the most dangerous cyber and financial crimes in the modern era, and to demonstrate the significant role that cybersecurity plays in combating it, as it is one of the effective ways to reduce it. In addition, it addresses the role of rapid technological progress, which has facilitated the commission of these crimes in all their forms. This development can be considered both a blessing and a curse at the same time. Accordingly, it can be said that while these modern technologies improve the efficiency and quality of work and foster innovation, they also cause significant security vulnerabilities that can be exploited by cybercriminals. This has led to cybersecurity facing numerous and significant challenges. Perhaps the phenomenon of electronic blackmail of women is one of the most dangerous and prominent of these. It has recently invaded Libyan society in an alarming way and through various methods. The misuse of the internet has led to the emergence of a group of users who seek to dedicate their efforts to adapting this technology to serve their self-serving interests by blackmailing internet users, through the use of vulgar methods that may be emotional or material to lure victims. They threaten victims by publishing embarrassing or confidential information, or by disabling their phone or computer systems, to force them to pay money, provide services, or gain illicit benefits, whether material or otherwise. Their methods vary, ranging from ransomware and distributed denial-of-service attacks to threats of publishing personal information. These tactics typically begin with entrapment or hacking and end with threats and extortion. It's worth noting that these tactics encompass various forms, including financial, emotional, and social blackmail. This necessitates heightened security awareness, strict laws, and close cooperation between individuals and security agencies to protect people and digital assets from this imminent danger. Individuals should report such incidents immediately and preserve evidence.
Keywords: Cybercrime, Cyber Extortion, Cybersecurity, Technological Development, Digital Space